A note on commutativity of automorphisms - M. S. Samman; M. Anwar Chaudhry; A. B. Thaheem (International Journal of Mathematics and Mathematical Sciences)
Let α and β automorphisms of a ring satisfying the equation α+α−1=β+β−1. In this paper we prove some results where this equation itself implies the commutativity of α and β.